2021
DOI: 10.1021/acs.jafc.1c06304
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid A To Alleviate Neuroinflammation of Alzheimer’s Disease in Mice by Regulating the Imbalance of the Th17/Tregs Axis

Abstract: Ganoderic acid A (GAA) is a kind of lanostane-type triterpenoid isolated from Ganoderma lucidum. Imbalance of the Th17/Tregs axis exists in the progress of neuroinflammation of Alzheimer's disease (AD). In this study, the alleviating neuroinflammatory effect of GAA on D-galactose mice was studied from the aspect of regulating the imbalance of the Th17/Tregs axis. The Morris water maze test was used to evaluate the cognitive ability of AD mice. Flow cytometry was used to detect the percentages of IL-17A, IL-17F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Ganoderic acid A reduces Aβ42 levels in microglia cells by enhancing autophagy via the Axl/Pak1 signaling pathway. Ganoderic acid A ameliorates cognitive deficiency in the AD mouse model and even reduces Aβ42 in mouse 30 . Yue et al (2021) showed that ganoderic acid A attenuates LPS‐induced neuroinflammation in BV2 microglia by activating the farnesoid X receptor (FXR) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderic acid A reduces Aβ42 levels in microglia cells by enhancing autophagy via the Axl/Pak1 signaling pathway. Ganoderic acid A ameliorates cognitive deficiency in the AD mouse model and even reduces Aβ42 in mouse 30 . Yue et al (2021) showed that ganoderic acid A attenuates LPS‐induced neuroinflammation in BV2 microglia by activating the farnesoid X receptor (FXR) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenes are one of the main and important active ingredients of G. lucidum , which can inhibit inflammatory responses, including peripheral [ 60 ] and brain inflammation. Previous studies show that ganoderic acid A ameliorates LPS-induced neuroinflammation by activating the farnesoid x receptor in vitro [ 61 ] and balances the Th17/Tregs axis to attenuate the neuroinflammation of Alzheimer’s disease in mice [ 23 ]. Deacetyl ganoderic acid F, another kind of triterpene obtained from G. lucidum , was found to suppress LPS-induced neural inflammation in vivo and significantly reduce the expression of inflammatory factors in the peripheral serum of mice [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a category of the main bioactive and medicative components in G. lucidum , Ganoderma lucidum triterpenoids (GLTs) are documented to perform various pharmacological actions such as anticancer [ 11 ], anti-inflammation [ 12 , 13 ], anti-atherosclerosis [ 14 ], anti-hyperlipidemia [ 15 ], antioxidants [ 16 , 17 ], antivirus [ 18 ], hepatoprotection [ 19 ], retardation renal cyst [ 20 ], renal fibrosis development, and protection of renal ischemia-reperfusion injury [ 21 ]. Moreover, recent studies evidence that GLTs can also exert pharmacological effects on the nervous system, alleviating neuronal apoptosis [ 22 ] and neuroinflammation [ 23 ] in Alzheimer’s disease mice. As components of GLTs, ganoderic acid [ 24 ] and deacetyl ganoderic acid F [ 25 ] were found respectively to improve 5-fluorouracil-induced cognitive dysfunction and inhibit lipopolysaccharide (LPS)-induced neural inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds from plants could reduce the associated neuroinflammation in AD. For example, acid alpha-glucosidase (GAA), a kind of lanostane-type triterpenoid isolated from Ganoderma lucidum, was found to have an alleviating neuroinflammatory effect on AD mice via regulating the imbalance of the Th17/Tregs axis [ 96 ]. OMT, an alkaloid component extracted from the root of Sophora flavescens Ait, could reduce the level of pro-inflammatory cytokines including IL-6, IL-1β, TNF-α and IL-17A in AD mice [ 97 ].…”
Section: The Function Of Th17 Cells and Il-17amentioning
confidence: 99%